Evaluation of a knemometer - Zöllner, Ekkehard Werner Arthur (Department of Paediatrics and Child Health, 2024)
Knemometry is a sensitive technique to measure lower leg length. It has been utilised in the assessment of short-term growth. Knemometry is compared to other indicators of early growth. Its uses and limitations are highlighted. 11 The acquisition of a knemometer necessitated a study to establish the reliability and the validity of its measurements, to compare two different recommended measuring procedures and to establish whether repositioning the child between readings is necessary. Forty-four healthy children ranging in age from 5,2 - 10,9 years were enrolled. Measurements were done by a single observer. The lower leg of each child was measured by a series of 3x3 readings called "measuring procedure 1" (MP1), followed by a series of 4 readings, the child being repositioned between each reading, called "measuring procedure 2" (MP2). Ten metal rods were measured at the start of each measuring day (314,90 - 449,90mm) to assess validity of the measurements. The mean standard deviation (SD) of the measurements performed on children was 0,4mm and the coefficient of variation (CV) 0,1%, irrespective of the measuring procedure. Rod measurements yielded corresponding values of0,13mm and 0,03%. The SD tended to increase with increasing length of rods (rod size 404,90 to 449,90mm). The measurement bias was -0,26mm, except for rod size 345mm (+0,07mm). The standard error of the mean when measuring children was lower for MP2 (0,20mm) than for MP1 (0,25mm). Outliers were distributed at random among the readings. Data analysis by one way ANOVA showed that it may be advantageous to reposition the subject in between readings. The results confirm that the knemometer is a sensitive instrument. Most of the variation in the measurements was attributable to the subjects, rather than the instrument. This could be explained by unidentified minor movements and by the relative "elasticity" of the children compared to the rods. The knemometer is less reliable in the upper range of measurement when rods are measured. The bias is not consistent, reflecting a possible weakness in the construction. Inspection identified the coupling arm of the knee plate as a possible source. Because outliers cannot be excluded while performing routine measurements, the 95th percentile for SD affords reasonable protection against their inclusion. It is recommended that 4 independent readings should be taken to establish a measurement and that the first reading should not be excluded. The whole series of readings should be repeated if the SD is >0,65mm. Users need to be aware of the construction flaw in the make of the instrument tested.